The CCR5 Gene Edited CD34+CD90+ Hematopoietic Stem Cell Population Serves as an Optimal Graft Source for HIV Gene Therapy - Karuppusamy, Karthik V.; Demosthenes, John Paul; Venkatesan, Vigneshwaran; Christopher, Abisha Crystal; Babu, Prathibha; Azhagiri, Manojkumar K.; Jacob, Annlin; Ramalingam, Veena Vadhini; Rangaraj, Sumathi; Murugesan, Mohankumar Kumarasamypet; Marepally, Srujan Kumar; Varghese, George M.; et al. (Frontiers in Immunology, 2022)
Transplantation of allogenic hematopoietic stem and progenitor cells (HSPCs) with C-C chemokine receptor type 5 (CCR5) Δ32 genotype generates HIV-1 resistant immune cells. CCR5 gene edited autologous HSPCs can be a potential alternative to hematopoietic stem cell transplantation (HSCT) from HLA-matched CCR5 null donor. However, the clinical application of gene edited autologous HSPCs is critically limited by the quality of the graft, as HIV also infects the HSPCs. In this study, by using mobilized HSPCs from healthy donors, we show that the CD34+CD90+ hematopoietic stem cells (HSCs) express 7-fold lower CD4/CCR5 HIV receptors, higher levels of SAMHD1 anti-viral restriction factor, and possess lower susceptibility to HIV infection than the CD34+CD90- hematopoietic progenitor cells. Further, the treatment with small molecule cocktail of Resveratrol, UM729 and SR1(RUS) improved the in vivo engraftment potential of CD34+CD90+ HSCs. To demonstrate that CD34+CD90+ HSC population as an ideal graft for HIV gene therapy, we sort purified CD34+CD90+ HSCs, treated with RUS and then gene edited the CCR5 with single sgRNA. On transplantation, 100,000 CD34+CD90+ HSCs were sufficient for long-term repopulation of the entire bone marrow of NBSGW mice. Importantly, the gene editing efficiency of ~90% in the infused product was maintained in vivo, facilitating the generation of CCR5 null immune cells, resistant to HIV infection. Altogether, CCR5 gene editing of CD34+CD90+ HSCs provide an ideal gene manipulation strategy for autologous HSCT based gene therapy for HIV infection.